Promoting and/or evading change: the role of student-staff partnerships in staff teaching development. Issue 10 (26th November 2019) - Marquis, Elizabeth; Power, Emily; Yin, Melanie
ABSTRACT: While a large body of research considers factors enabling or constraining academic development in colleges and universities, comparatively little scholarship has considered the roles students might play in supporting positive change in staff teaching practices. This article explores one potential avenue by which such change might play out, considering the extent to which participation in a student-staff partnership programme supported by a central teaching and learning institute might encourage shifts in staff teaching. Drawing on data gathered via focus groups and online reflective prompts, we find that participating in pedagogical partnership can support a range of developments in staff teaching practices, though these changes might not always be pronounced or uniformly positive. Implications for future research and practice are discussed.